Anti-phospholipase A2 receptor antibodies: Current applications in primary membranous nephropathy - Relvas,Miguel (2020)
Background: Membranous nephropathy (MN) is among the most common causes of nephrotic syndrome in nondiabetic adults. The podocytic M-type phospholipase A2 receptor (PLA2R) has been identified as the major antigenic target of the immune response that underlies primary membranous nephropathy (PMN). In the last decade, anti-PLA2R antibodies have been seen as promising diagnostic biomarkers for PMN. Other potential uses include assessment of disease activity and prognosis, therapeutic monitoring and prediction of disease recurrence after renal transplant. Objective: To review clinical studies exploring the current role of anti-PLA2R antibodies. Methods: This systematic review was conducted according to PRISMA guidelines. Two databases were searched for articles published between January 2010 and August 2019. Fifty-one studies met the inclusion criteria. Results: Anti-PLA2R antibodies constitute highly sensitive and specific markers for PMN. Antibody titers correlate positively with disease activity. Low levels or seronegativity correlate to higher remission rates. Relative reduction of antibody titers seems to correlate with the likelihood of response to therapy. The value of this antibody in the prediction of post-transplant recurrence is uncertain, as is its use in the pediatric population. Conclusion: Anti-PLA2R antibodies are assuming an increasingly important role in MN management. Anti-PLA2R positivity in the context of nephrotic syndrome is very suggestive of PMN diagnosis. Nevertheless, further efforts are required to define optimal cut-off values for seropositivity and risk stratification.